ANALISIS ETIKA PELAYANAN DALAM MEWUJUDKAN GOOD GOVERNANCE DI KECAMATAN TANJUNGSARI KABUPATEN SUMEDANG - Muhamad Rizqy Sopandi (LPPM UNSAP, 2026)
Public service ethics play an important role in realizing the principles of good governance, such as accountability, transparency, and responsiveness. This study aims to analyze the implementation of public service ethics, identify obstacles in its implementation, and evaluate efforts made to overcome these obstacles in Tanjungsari Subdistrict, Sumedang Regency. This study uses a qualitative approach with a descriptive method. Data analysis techniques are based on the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. Data was collected through in-depth interviews with five informants (the subdistrict head, the subdistrict secretary, public service staff, and two community members), supported by observations and documentation. The results of the study indicate that the implementation of public service ethics has been quite successful, guided by the principles of Equality, Equity, Loyalty, and Responsibility according to Mertins Jr. (2003), which are reflected in fair, non-discriminatory attitudes and the responsibility of public servants toward public service; obstacles in the implementation of ethics stem from personal factors, such as low integrity and lack of understanding of ethics, as well as organizational factors, such as a permissive work culture and weak leadership role models, as explained by Terry L. Cooper (2012); improvement efforts are carried out through ethics training, integrity development, strengthening organizational culture, and ethical leadership. This study recommends the need for a more systematic and sustainable approach in strengthening public service ethics, so that the principles of good governance can be optimally realized at the sub-district level.